Real-world study of phakic refractive lens for correction of high myopia - An-Peng Pan; Xu Shao; Yi-Ke Li; Zi-Yue Li; Qiong Yan; Wei-Yang Sun; A-Yong Yu (Eye and Vision)
Abstract Background To assess the safety and efficacy of phakic refractive lens (PRL) implantation for correcting high myopia, as well as an ophthalmic viscosurgical device-free (OVD-free) method for PRL implantation. Methods In this real-world prospective study, consecutive patients implanted with PRL in one or both eyes were enrolled. Based on the surgical techniques used, the eyes were divided into the OVD-free method group and the conventional method group. The patients were examined 2 h after surgery and were scheduled for follow-up at 1 day, 1 week, 1 month, 3 months, 6 months, and 12 months. The corrected distance visual acuity (CDVA), uncorrected distance visual acuity (UDVA), the manifest refraction spherical equivalent (MRSE), intraocular pressure (IOP) and lens vault were assessed postoperatively. Corneal endothelial cell density (ECD) was measured at the 3- and 12-month postoperative visits. Results Fifty-seven consecutive patients (108 eyes) were enrolled. At the 3-month postoperative visit, both mean UDVA and CDVA were significantly improved after PRL implantation (0.19 ± 0.21 and 0.01 ± 0.14 logMAR) with efficacy index and safety index of 0.92 and 1.30, respectively. None of the eyes had any loss of CDVA. The percentage of eyes within ± 0.50 D and ± 1.00 D of target refraction was 58% and 83%, respectively. Mean MRSE changed from − 14.49 ± 4.22 D, preoperatively, to − 1.22 ± 1.26 D at 1 day (P < 0.001) and remained stable thereafter. Mean endothelial cell loss was 11.3%, 9.6%, respectively, at 3 and 12 months, with no significant difference between the two follow-ups (P = 0.395). Fifty-nine eyes received the OVD-free method, and 49 eyes received the conventional method. The OVD-free method demonstrated a significant reduction in the incidence of early acute IOP elevations (28.8% vs. 53.1%, P = 0.022) compared to the conventional method. The difference of initial endothelial cell loss (9.4 ± 14.2% vs. 13.6 ± 14.6%) between the two groups trended toward significance (P = 0.056). In both groups, no other major complications were observed up to 12-month follow-up. Conclusions PRL implantation was a safe, efficient, predictable and stable method for correcting high myopia. The potential of lower incidence of early acute IOP elevations makes the OVD-free method a promising alternative to the conventional method. Trail registration: Chinese Clinical Trial Registry, ChiCTR2100043600. Registered on 23 February 2021, https://www.chictr.org.cn/showproj.html?proj=122229